2019
DOI: 10.1088/1757-899x/621/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of Danau Kota Lake water quality using chemometrics approach

Abstract: Danau Kota Lake is public attraction area, located in the middle area of Kuala Lumpur. An excessive count of visitors visiting the lake has weakening the lake water quality. The present study was driven to evaluate the lake water quality for environmental conservation. Some water quality and metals data were in-situ measured whereas some were collected for laboratory analysis. BOD, OG, AN and TC are identified as major pollutants towards Danau Kota Lake water quality. The decreasing concentration of DO and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In stepwise selection, the two techniques are combined as variables are added one at a time. The variables are re-examined at each step to determine if any have become redundant and will be dropped (Juahir et al 2018).…”
Section: Discriminant Analysismentioning
confidence: 99%
“…In stepwise selection, the two techniques are combined as variables are added one at a time. The variables are re-examined at each step to determine if any have become redundant and will be dropped (Juahir et al 2018).…”
Section: Discriminant Analysismentioning
confidence: 99%
“…Numerous studies reported salinity distribution and interference are the pivotal environmental factors influencing the survival and distribution of species in estuaries [10,11]. Since salinity is a conservative material, its time and space variance would be primarily due to its advection and flow dispersion [12,13]. Naturally, the seawater intrusion into river mouths mostly due to increasing sea levels, river discharge and breaching coastal areas [14,15].…”
Section: Water Salinity Modelmentioning
confidence: 99%
“…In 2012, the Malaysian government imposed new rainwater harvesting system at large commercial and residential buildings, such as bungalows and semi-detached houses, to install a rainwater harvesting system under the Uniform Building By-Laws 1984 [44]. [45][46][47][48]. To date, limited studies were reported where multivariate statistical techniques were applied in rainwater study.…”
Section: East Malaysia Climate and Rainwater Blessingmentioning
confidence: 99%